Efficacy and safety of keishibukuryogan, a traditional Japanese Kampo medicine, for hot flashes in prostate cancer patients receiving androgen deprivation therapy - Shigehara, Kazuyoshi (Transl Androl Urol, 2020)
BACKGROUND: The efficacy and safety of keishibukuryogan, a traditional Japanese medicine, were investigated for the treatment of hot flashes in prostate cancer (PC) patients receiving androgen deprivation therapy. METHODS: Thirty patients were enrolled and orally administered 2.5 g keishibukuryogan three times daily for 12 weeks. The frequency, strength, and duration of hot flashes were self-evaluated by the patients in a diary every 4 weeks. All patients also completed a questionnaire to determine their aging male symptoms (AMS) scale score and underwent blood biochemical testing. RESULTS: Twenty-five patients completed the 12-week treatment. Hot flash strength significantly improved 4, 8, and 12 weeks after treatment. Their frequency was significantly reduced at the 8-week visit, and duration was significantly shorter after the 8-week visit. In addition, the score of the AMS somatic subscale was improved at the 8- and 12-week visits. Among the somatic items, questions 3 (excessive sweating) and 5 (increased need for sleep) were significantly improved. Obesity, radiation, and a longer duration of PC were predictive factors for treatment response. Prostate specific antigen and total testosterone levels were unchanged, and no patients had severe adverse effects. CONCLUSIONS: Keishibukuryogan was an effective and safe treatment for hot flashes in PC patients.